THE ROLE OF SOCIAL NETWORKS FOR VETERANS WITH SPINAL CORD INJURY IN OBTAINING EMPLOYMENT. Issue 2 (November 2013) - Cotner, Bridget A.; Keleher, Jennie; O'Connor, Danielle R.; Trainor, John K.; Ottomanelli, Lisa; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> The purpose of this article is to demonstrate the use of ethnographic methods to explore the types of social support provided to Veterans with spinal cord injuries (SCIs) who are participating in an employment program. Interview data with Veterans and their social support members along with employment narratives written after a job was secured are used to document the types of support provided to Veterans with SCI to facilitate obtaining and maintaining employment. The impact of social support on mental and physical health is well documented in the literature; however, there is a need for research on the influence of social support on employment. As applied in VA spinal cord care, the "individual placement and support (IPS)" model of supported employment for vocational rehabilitation integrates vocational services into clinical treatment, and includes social support members in the pursuit of employment goals. Guided by theories of social capital, the types of social support provided to Veterans were classified into three types: instrumental, informational, and emotional. Analysis of data showed that for all Veterans with SCI, some form of social support was needed to aid in finding and maintaining employment, demonstrating the need for evidence‐based supported employment (EBSE) services in the VA spinal cord system of care.